A Wireless Communication System with High Reliability and Low Latency for the Internet of Things: Issues, Foundations, and Technologies - Mohapatra, Priyabrata (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
The Internet of Things (IoT) has seen substantial technological and application development. By 2020, it is predicted that wireless IoT networks will connect more than 25 billion devices. The whole communication protocol stack for wireless IoT networks has to be reconsidered directly in the research, researchers examine numerous HRLL wireless IoT network application scenarios, underlying performance constraints, and possible future technologies. Researchers also get across the network structure that has been adjusted to reduce latency. Many IoT applications, such as industrial automation, vehicle-to-everything (V2X) networks, smart grids, and remote surgery, will demand strict transmission latency and reliability requirements in addition to ubiquitous connectivity, which may not be provided by current systems. Because they need low-latency, high-reliability links to maintain stability, high-performance internet of things control systems with tens to hundreds of sensors and actuators use wired connections between all of their parts. However, the wires lead to many reliability issues that switching to wireless links would solve. So, they are made for either high-throughput or low power communication between a pair or a limited number of terminals, current or proposed wireless system can provide the latency and dependability required by the control algorithms. It is proposed to employ low-rate coding, semi-fixed resource allocation, and reliable broadcasting to achieve low-latency operation in a wireless system. The sixth-generation (6G) system, a new wireless communication paradigm with full AI support, is anticipated to be put into use between 2027 and 2030. Beyond 5G, some essential concerns that need to be solved include larger systems capacity, faster data rate, lower latency, higher security, and enhanced quality of service (QoS) compared to the 5G system. The number of wireless gadgets will exceed the number of people in the near future, and most of these devices will communicate with each other rather than with humans. The Internet of Things (IoT) will require low-latency, high-reliability communication with reasonable data rates. High-performance industrial control is one of the few applications that have IoT-like needs at this time. People-centric networks don't require high data speeds to function closed loop. As providing low-latency and high-reliability operation for a significant number of users, present WLAN and cellular systems struggle. An early wireless system architecture is intended to address this problem. Utilizing numerous, cooperating access points that are dispersed across the system, similar to coordinated multipoint in cellular networks, is one possibility. Another choice is based on distributed space-time codes. The second section of the paper examines the analogue front end, modulation, baseband processing, and multiple access protocol as they relate to constructing the physical layer of the suggested cooperative relaying system architecture. The use of as many building pieces from existing systems as feasible is prioritized. High-reliability wireless systems must have efficient hardware, and error control decoders are a crucial component. The construction of a low-latency, low-power LDPC decoder for the IEEE 802.11ad standard, whose LDPC codes include numerous properties suitable to wireless control, is covered in the third section of this study. The decoders deeply pipelined, highly parallel, coding architecture strikes a balance between power and latency. Row-merging, multi-codeword processing simultaneously, lower memory accuracy due to marginalization, and back-biasing to effectively balance active and leakage power further cut down on latency and power. Authors give a thorough explanation of the functions of 6G in several fields many potential IoT applications across five core categories, including the Internet of Things for Healthcare and the Internet of Things for Vehicles and Satellite, Unmanned Aerial Vehicles, and Autonomous Driving Industrial Internet of Things.
Keywords: High-reliability and low-latency wireless communication; Internet of Things (IoT); MAC layer; network layer; physical layer